IMPLEMENTASI KEBIJAKAN BUMDES DALAM MENINGKATKAN PEREKONOMIAN MASYARAKAT MELALUI PENGELOLAAN SAMPAH DI DESA BANGUNREJO KABUPATEN KENDAL - Rizzal Firmanudin; Maulida Putri Rahmawati; Suprihatma (Halu Oleo University, 2022)
This research was conducted in Bangunrejo Village, Patebon District, Kendal Regency. This study aims to determine how the implementation of Village Owned Enterprises (BUMDes) policies in Bangunrejo Village, Kendal Regency. in the process of a good waste management unit and have carried out the correct procedures so that in the future they can turn the waste management unit into waste processing to improve the economy of the people of Bangunrejo Village. Therefore, research related to policy implementation at BUMDes Bangun Karya was carried out. This study uses Mariiee S. Grindle's theory of policy implementation, namely implementation which is influenced by two variables, namely the policy content variable (content) and the policy environment (context). The data collection techniques are observation and interviews which are then processed and analyzed qualitatively. In collecting interview data, it was carried out in Bangunrejo Village, Kendal Regency. The results of this study are: (1) the driving and inhibiting factors for the implementation of the BUMDes policy of the waste management unit are still constrained by the limited tools needed for good waste management in order to improve the community's economy (2) The role of the community is very important in the success of the BUMDes waste management unit so that can improve the economy of the community and village